2022
DOI: 10.1016/j.scitotenv.2021.149577
|View full text |Cite
|
Sign up to set email alerts
|

Restoration impacts on rates of denitrification and greenhouse gas fluxes from tropical coastal wetlands

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 91 publications
1
6
0
Order By: Relevance
“…Changes in wetland carbon pools are influenced by environmental factors such as temperature [11], water level [29], and soil nutrients. Clarifying the magnitude and seasonal variation of SOC and its main influential factors in the lakeside zone is of significance both to accurately evaluate the role of wetland ecosystems in global climate change and to deeply understand the mechanisms of carbon pool changes in wetland ecosystems [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in wetland carbon pools are influenced by environmental factors such as temperature [11], water level [29], and soil nutrients. Clarifying the magnitude and seasonal variation of SOC and its main influential factors in the lakeside zone is of significance both to accurately evaluate the role of wetland ecosystems in global climate change and to deeply understand the mechanisms of carbon pool changes in wetland ecosystems [2].…”
Section: Discussionmentioning
confidence: 99%
“…Wetlands are a type of ecosystem located between water bodies and land and are known as one of the three major ecosystems along with forests and oceans [1]. The ecosystem service function of wetlands is currently declining, and wetland restoration has thus become a hot topic [2,3]. The effective implementation of wetland restoration requires an in-depth study of the ecological process of wetland systems.…”
Section: Introductionmentioning
confidence: 99%
“…Long‐term (15 years) measurements of an urbanization‐impacted lake showed that p CO 2 variation negatively responded to environmental investment, indicating that watershed management may slow CO 2 emissions from artificially controlled inland waters (Xiao, Duan, et al., 2020). Another study found that restoration has a negligible influence on CO 2 effluxes in coastal wetlands (Comer‐Warner et al., 2022). In some studies of metropolitan river networks, the average CO 2 saturation and evasion in rivers located in urban areas, on a holistic level, were more than three times higher than those in rural and forest areas, but CO 2 saturation in urban rivers showed much larger variability than that in nonurban rivers (X. Wang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…9–10). Importantly, information on the development of soil denitrification as restoration progresses and, thus, the capacity of the restored wetland to improve water quality is limited (Comer‐Warner et al, 2022 , pp. 10–11).…”
Section: Introductionmentioning
confidence: 99%